2020
DOI: 10.1186/s41182-020-00253-4
|View full text |Cite
|
Sign up to set email alerts
|

Diarrheal morbidity and predisposing factors among children under 5 years of age in rural East Ethiopia

Abstract: Background: Diarrheal diseases remain a leading cause of preventable death among children under-five in lowand middle-income countries (LMICs). In Ethiopia, diarrhea is the major contributor to deaths for children under the age of 5 years. In order to develop prevention strategies for the alleviation of childhood diarrhea, it is necessary to identify the important predisposing factors. These predisposing factors have been observed to vary by location across Eastern Ethiopia. Moreover, the evidence on prevalenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 23 publications
2
20
0
Order By: Relevance
“…In this study, the odds of diarrhea were higher among children whose mothers had no formal education and lower educational status than children whose mothers had higher education. The study findings are consistent with earlier studies, which found higher odds of childhood diarrhea among children whose mothers were of lower educational status in Ethiopia, 5 , 7 , 11 , 42 , 43 Ghana, 44 and Uganda. 45 These observations may be due to well-educated mothers who are more likely to have better experience, education, attitude, and the necessary health information required for the appropriate diarrheal prevention.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In this study, the odds of diarrhea were higher among children whose mothers had no formal education and lower educational status than children whose mothers had higher education. The study findings are consistent with earlier studies, which found higher odds of childhood diarrhea among children whose mothers were of lower educational status in Ethiopia, 5 , 7 , 11 , 42 , 43 Ghana, 44 and Uganda. 45 These observations may be due to well-educated mothers who are more likely to have better experience, education, attitude, and the necessary health information required for the appropriate diarrheal prevention.…”
Section: Discussionsupporting
confidence: 92%
“…In Ethiopia, diarrhea is the major contributor to the deaths of children under the age of 5 years. Key determinants of diarrhea among under 5 children in Ethiopia included lack of latrine, 5 , 6 maternal hand-washing practice after visiting a toilet, 5 , 7 , 8 child and maternal factors, 5 , 9 - 13 and socioeconomic factors. 13 According to the Ethiopian Demographic and Health Survey (EDHS) reports, the prevalence of diarrhea in 2000, 2005, 2011, and 2016 in under-5 Ethiopian children was 26%, 18%, 14%, and 12%, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Were consistent with the findings of the current study in titled (diarrheal morbidity and predisposing factors among children under 5 years of age in rural East Ethiopia). They mentioned that the majority of mother housewife and accounted for (73.6) [10] .…”
Section: Discussion Of Socio-demographic Characteristics For Mothers (In the Table 1)mentioning
confidence: 99%